Perancangan Sistem Informasi Pembayaran Angsuran Kredit Kendaraan Berbasis Multiuser Pada Yamaha Langgeng Motor Ungaran - Kustiyono, Kustiyono (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
This research is to obtain an overview of the development of information technology that is so rapid and fast and easier that can be applied or used in the Yamaha Langgeng Motor vehicle Dealer Company in Ungaran to take advantage of computer facilities as a tool to help record sales, both cash and credit, and also to installment payments, because it will help speed up service, data storage to a more secure database archive. Thus it is necessary to have a system that records installment payments regarding: item data (motorbikes), sales data both cash and credit and installment payment data, using the Microsoft Visual Basic 6.0 programming language and My Sql database. The advantage of this new system is that vehicle data, consumer data, sales data both cash and credit and instalment payments will be well databased so that if at any time a consumer comes to pay, it turns out that he does not bring the old payment receipt, the previous administration does not bother to look for the next payment, because it can be seen directly on the system.